PENGARUH KETRAMPILAN PROSES SAINS TERINTEGRASI KARAKTER TERHADAP HASIL BELAJAR FISIKA - Imas Ratna Ermawati; Agnesia Bergita Anomeisa; Hendrik Seputra (Jurnal Pendidikan Fisika, 2019)
This research was conducted to find out whether the test of science process skill integrated character to influence on high school physics learning result. The research was conducted at SMAN 1 Maumere in class XI MIA 1 as experiment class and XI MIA 2 as control class with material that is optical equipments in the even semester of academic year 2017/2018. The research method used is experiment with Quasi Experimental Quasi Experimental Experimental design that used is The Noneequivalent Pretest-Posttest Control Group Design ,, while the research subject taking technique is Simple Random Sampling. Research subjects used amounted to 33 students both from the experimental class and control class. Before the research instrument is used first tested the validity and reliability test. In the validity test using Product Moment Pearson correlation, there are 24 tested questions and obtained the result of 18 valid questions and 6 drop problems. In reliability test by using Cronbach Alpha formula in get result rhitung = 0,870> 0,329; so the instrument is said to reliab with high interpretation. The next stage conducted data retrieval using instruments that have been valid and reliable then tested the prerequisite analysis in the form of normality test and homogeneity test. In the normality test using chi square obtained results; with a significant level of α = 0.05 and a sample size of 33 students in the experimental class and in the control class which means that the experimental and control classes are normally distributed. On the homogeneity test using F test obtained the results,; with a significant level α = 0.05 and the number of samples of 33 students then the class of research is a homogeneous class. In the last stage, hypothesis testing with t-test and obtained the result,; with significant level α = 0.05 and the number of samples as many as 33 students, the skills of integrated science processes developed characters that influence the results of physics learning.